Data-driven professional factors for ACI 318 one-way shear strength. Issue 9 (2nd September 2023) - Aguilar, Victor; Barnes, Robert W.; Nowak, Andrzej S.
Abstract: Uncertainty is inherent in analytical models because of simplifications and approximations, and this uncertainty is referred to as the professional factor in reliability analyses context. In the past, a lack of agreement regarding the accuracy of the ACI 318 building code requirements for structural concrete one-way shear equations made meaningful calibration of a shear resistance factor for design unjustifiable. Only expert opinion estimation of professional factors was available. Recently, in the latest edition of the ACI 318, the one-way shear design equations for reinforced concrete members significantly changed. This paper describes an effort to determine data-driven professional factors that characterize the previous and new ACI 318 analytical models for one-way shear strength. The resulting professional factors were determined through analysis of the extensive joint DAfStb-ACI Committee 445-D Shear database. The proposed, data-driven professional factors are markedly different than the subjective, expert-opinion professional factors proposed in the past. Furthermore, the analyses indicate that the new ACI 318-19 one-way shear equations represent an improvement across the full range of member sizes—especially for members without shear reinforcement. Therefore, a reliability-based calibration of the ACI 318 one-way shear resistance factor using the proposed professional factors is warranted.